2016
DOI: 10.1097/md.0000000000003054
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Fibrillation is Associated With Poor Outcomes in Thrombolyzed Patients With Acute Ischemic Stroke

Abstract: The influence of atrial fibrillation (AF) on the clinical outcomes of patients with ischemic stroke (IS) has not been completely determined. We aimed to perform a systematic review and meta-analysis to assess the relationship between AF and adverse events in patients with acute IS treated with thrombolysis.PubMed, EMBASE, and the Cochrane Library were searched for relevant studies regarding the association between AF and the outcomes of patients with IS treated with thrombolysis. Random and fixed effect models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 28 publications
8
24
0
Order By: Relevance
“…Presence of specific comorbidities can affect functional outcomes following stroke. For example, a meta-analysis of 12 longitudinal cohorts following stroke thrombolysis, comprising 14,801 patients, found that AF was associated with a reduced likelihood of favourable outcome (modified Rankin Scale ≤2) 27 .…”
Section: Functional Outcomesmentioning
confidence: 99%
“…Presence of specific comorbidities can affect functional outcomes following stroke. For example, a meta-analysis of 12 longitudinal cohorts following stroke thrombolysis, comprising 14,801 patients, found that AF was associated with a reduced likelihood of favourable outcome (modified Rankin Scale ≤2) 27 .…”
Section: Functional Outcomesmentioning
confidence: 99%
“…IVT has been reported to increase the incidence of HT markedly [7]. Atrial fibrillation (AF) [8,9], National Institutes of Health Stroke Scale (NIHSS) score [10], blood glucose level [11], leukoaraiosis [12], dual antiplatelet agent treatment before IVT [13], and systolic blood pressure variability [14] are the predictors of HT after IVT.…”
Section: Introductionmentioning
confidence: 99%
“…AF appears to be an independent risk factor of in-hospital mortality, length of hospital stay, and increased treatment costs in stroke patients [26]. Kimura [28]. With the increase of studies of thrombolysis in AF, we collected more evidence to compare the outcomes of thrombolysis in patients with AF and non-AF, and to compare the outcomes of thrombolytic and nonthrombolytic therapy in patients with AF.…”
Section: Discussionmentioning
confidence: 99%